A case study on Prudential Assurance Malaysia Berhad towards factors on achieving its goals as a successful agent / Mohd Nashriq Shaharom - Shaharom, Mohd Nashriq (Faculty of Business and Management, 2010)
This research was conducted for the purposed of finding the “strength to become the successful wealth planner in Prudential Assurance Berhad, Melaka”. The main objective of this research was to determine the various factors to become successful wealth planner. Those factors are the listening skills, personal planning, time management, communication skills and closing skills.The respondent of this study would be the wealth planner in the Prudential Assurance Berhad in Melaka only.